1998
DOI: 10.1037/0021-9010.83.2.247
|View full text |Cite
|
Sign up to set email alerts
|

The effects of organizational citizenship behavior on performance judgments: A field study and a laboratory experiment.

Abstract: The process linking organizational citizenship behavior (OCB) with performance judgments was investigated in a field and a laboratory study. In the field study, managers rated the task performance and OCB of 148 subordinates. In the laboratory research, 136 students viewed and rated videotaped segments of teaching performance that demonstrated either high or low task performance and high or low OCB. In both studies, liking and perceived affective commitment mediated the relationship between OCB and overall eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
481
3
13

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(528 citation statements)
references
References 50 publications
31
481
3
13
Order By: Relevance
“…Existing research shows that performance appraisal is significantly influenced by supervisor attribution of employees' motives for exhibiting certain behaviors [22,23]. Not only the identification of specific motives, but also the types of attributed motives influence supervisors' evaluations of subordinates [11].…”
Section: Attribution Of the Motives And Performance Appraisal Of Emplmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research shows that performance appraisal is significantly influenced by supervisor attribution of employees' motives for exhibiting certain behaviors [22,23]. Not only the identification of specific motives, but also the types of attributed motives influence supervisors' evaluations of subordinates [11].…”
Section: Attribution Of the Motives And Performance Appraisal Of Emplmentioning
confidence: 99%
“…In recent years, the attribution perspective has been widely used in the studies on organizational behavior [19][20][21]. The extant research has shown that performance appraisals are significantly influenced by the supervisor's attribution of an employee's motives behind certain behaviors [22,23], implying that when employees make suggestions and/or present new ideas, their motives will be perceived and attributed by supervisors, thereby influencing their performance appraisals.…”
Section: Introductionmentioning
confidence: 99%
“…Ces résultats incitent à ne prendre en compte que l'engagement affectif dans les discussions subséquentes. Ainsi, on remarque que les résultats liés à cette variable s'approchent de ceux obtenus dans plusieurs autres études (Allen et Rush, 1998 ;MacKenzie et al, 1998 ;Organ, 1997 ;Organ et Ryan, 1995 ;Podsakoff et al, 1996). Il convient de préciser cependant qu 'Organ (1997) associait l'engagement affectif à l'altruisme, ce qui ne semble pas être le cas dans la présente étude.…”
Section: Discussionunclassified
“…Il semble d'ailleurs que l'engagement organisationnel puisse être un prédicteur efficace des comportements de citoyenneté organisationnelle. En effet, une recension (Organ et Ryan, 1995) et sept études présentent des résultats qui mettent en évidence la relation entre ces deux variables (Allen et Rush, 1998 ;Bergami et Bagnozzi, 2000 ;Koh et al, 1995 ;MacKenzie et al, 1998 ;Organ, 1997 ;Podsakoff et al, 1996 ;Schappe, 1998).…”
Section: Engagement Organisationnelunclassified
“…Many researchers found that employee's motivation is considerably associated to his or her organizational citizenship behavior (Finkelstein and Penner, 2004;Tang and Ibrahim, 1998). Allen and Rush (1998) stated that the leader's perception of follower's motives is more likely to influence the employee's OCB rating. Thus a significant relationship is anticipated between employee OCB and their sources of motivation.…”
Section: Motivationmentioning
confidence: 99%